Real exchange rate as an unobservable variable - Pertti Haaparanta; Jarmo Kontulainen (Bank of Finland, 1989)
The Finnish real exchange rate is estimated as a latent variable in a model of current account determination. The measure thus constructed behaves in the 70's much like the measures most often used (relative unit labour costs and relative consumer prices) but in the 80·s there are considerable differences. This could be interpreted as indicating a structural change in the Finnish open sector.
URN:NBN:fi:bof-201807301760
Keywords: 330